The distribution and source of boulders on asteroid 4179 Toutatis. Issue Volume 10:Issue S318(2015) (1st March 2016) - Jiang, Yun; Ji, Jianghui; Huang, Jiangchuan; Marchi, Simone; Li, Yuan; Ip, Wing-Huen
Abstract: Boulders are ubiquitous on the surfaces of asteroids and their spatial and size distributions provide information for the geological evolution and collisional history of parent bodies. We identify more than 200 boulders on near-Earth asteroid 4179 Toutatis based on images obtained by Chang'e-2 flyby. The cumulative boulder size frequency distribution (SFD) gives a power-index of −4.4 ± 0.1, which is clearly steeper than those of boulders on Itokawa and Eros, indicating much high degree of fragmentation. Correlation analyses with craters suggest that most boulders cannot solely be produced as products of cratering, but are probably survived fragments from the parent body of Toutatis, accreted after its breakup. Similar to Itokawa, Toutatis probably has a rubble-pile structure, but owns a different preservation state of boulders.